Biochemical characterization of proliferative and differentiated SH-SY5Y cell line as a model for Parkinson's disease. (May 2021) - Alrashidi, Haya; Eaton, Simon; Heales, Simon
Abstract: Parkinson's disease is a multifactorial neurodegenerative disease. The cellular pathology includes dopamine depletion, decrease in mitochondrial complex I enzyme activity, lysosomal glucocerebrosidase enzyme activity and glutathione levels. The SH-SY5Y human neuroblastoma cell line is one of the most widely used cell line models for Parkinson's disease. However, the consensus on its suitability as a model in its proliferative or differentiated state is lacking. In this study, we characterized and compared the biochemical processes most often studied in PD. This in proliferative and differentiated phenotypes of SH-SY5Y cells and several differences were found. Most notably, extracellular dopamine metabolism was significantly higher in differentiated SH-SY5Y. Furthermore, there was a greater variability in glutathione levels in proliferative phenotype (+/- 49%) compared to differentiated (+/- 16%). Finally, enzyme activity assay revealed significant increase in the lysosomal enzyme glucocerebrosidase activity in differentiated phenotype. In contrast, our study has found similarities between the two phenotypes in mitochondrial electron transport chain activity and tyrosine hydroxylase protein expression. The results of this study demonstrate that despite coming from the same cell line, these cells possess some key differences in their biochemistry. This highlights the importance of careful characterization of relevant disease pathways to assess the suitability of cell lines, such as SH-SY5Y cells, for modelling PD or other diseases, i.e. when using the same cell line but different differentiation states. Highlights: Proliferative and differentiated SH-SY5Y cells exhibit biochemical differences. Tyrosine hydroxylase expression is comparable between the two phenotypes. Extracellular Dopamine turnover rate is higher in differentiated SH-SY5Y cells. Lysosomal glucocerebrosidase activity is higher in differentiated SH-SY5Y cells. Mitochondrial respiratory chain activity is similar between the two phenotypes.